Rare case of primary duodenal somatostatinoma - Subramaniam, Aravinth; Natesan, Anandvijai; Chinnusamy, Palanivelu; Gnanasekaran, Divya; Chittawadagi, Bharathi Bhushan (Indian Journal of Case Reports, 2019)
Neuroendocrine tumors develop from any part of the gastrointestinal tract. Duodenal neuroendocrine tumors constitute only 2.6% of all neuroendocrine tumors. Somatostatinomas are a type of neuroendocrine tumor. They are more common in the pancreas. We present a rare case of duodenal somatostatinoma. A 53-year-old male was presented with a complaint of upper abdominal pain. On evaluation, multi detector computed tomography showed heterogeneously enhancing hypodense mass in the medial wall of the second part of duodenum and head of pancreas measuring 3.1 × 2.8 cm. Whipples surgery was done and the microscopy showed neuroendocrine tumor with psammomatous calcification. On immunohistochemistry evaluation, the tumor cells were positive for Chromogranin, Synaptophysin, and Somatostatin. Hence, we reported this case as duodenal somatostatinoma.